Scorpiurus aramoana (Diptera: Dolichopodidae), a new species from New Zealand - Bickel, Daniel J.; Kerr, Douglas Steven (Zootaxa, 2018)
The New Zealand endemic genus Scorpiurus Parent is known from marine littoral habitats. A new species, S. aramoana sp. nov., is described from coastal Otago of the South Island. Males have diagnostic flattened and modified tarsomeres on legs I and II. A key is provided to the New Zealand genera of Hydrophorinae and the three described species of Scorpiurus.